Telecommunications Carriers and the “Duty to Serve” - Ryan, Michael (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2012)
Telephone companies share with other public utilities a common law duty to provide their services on demand, at a reasonable price, and without unreasonable discrimination. In Canada, this common law duty exists alongside statutory service obligations imposed on telecommunications carriers and regulatory policies promoting universal access to basic telecommunications services. Some argue that in the modern environment, where a wide range of telecommunications services is available on a near-universal basis from a profusion of suppliers, the duty to serve has become an anachronism and that carriers should now be relieved of such obligations. There are others, however, who caution that the elimination of the duty to serve might jeopardize the continuation of service to geographically remote areas and should therefore be retained. Still others advocate expanding the duty to include broadband in order to facilitate wider access to high-speed Internet services. The debates surrounding these issues reveal that there is no consensus about the scope of the duty to serve. This article seeks to clarify the parameters of the common law duty to serve and discusses how that duty interrelates with carriers’ statutory service obligations and regulatory policies promoting universal service.